Timing of smolt migration in sympatric populations of Atlantic salmon ( Salmo salar), brown trout ( Salmo trutta), and Arctic char ( Salvelinus alpinus) - Jensen, Arne J.; Finstad, Bengt; Fiske, Peder; Hvidsten, Nils Arne; Rikardsen, Audun H.; Saksgård, Laila (Canadian Journal of Fisheries and Aquatic Sciences, 2012)
A study over a 22-year period of first-time migrants (smolts) of three sympatric salmonids (Atlantic salmon ( Salmo salar ), brown trout ( Salmo trutta ), and Arctic char ( Salvelinus alpinus )) in a watercourse in northern Norway demonstrated that although there was considerable overlap in smolt migration timing among the species, Atlantic salmon migrated first, followed by Arctic char, and finally brown trout. The migration period of Arctic char had a smaller range and less annual variation than those of the two other species, possibly partly related to their more lake-dwelling habitat preference. For all species, water flow was important in explaining day-to-day variations in smolt runs. Water flow was most important for brown trout, change in flow for Atlantic salmon, whereas photoperiod was most important for Arctic char. These results suggest that both age and size of smolts and the timing of the smolt migration have been shaped by the different habitat preferences of these species both in fresh water and sea through local selection.